2020
DOI: 10.1111/jch.13948
|View full text |Cite
|
Sign up to set email alerts
|

Use of distinct anti‐hypertensive drugs and risk for COVID‐19 among hypertensive people: A population‐based cohort study in Southern Catalonia, Spain

Abstract: The use of some anti‐hypertensive drugs in the current COVID‐19 pandemic has become controversial. This study investigated possible relationships between anti‐hypertensive medications use and COVID‐19 infection risk in the ambulatory hypertensive population. This is a population‐based retrospective cohort study involving 34 936 hypertensive adults >50 years in Tarragona (Southern Catalonia, Spain) who were retrospectively followed through pandemic period (from 01/03/2020 to 30/04/2020). Two data sets including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…In a population based retrospective study of 34,936-hypertensive adults, the use of antihypertensive drugs, including diuretics, CCBs, βARBs, ACE-Inhs. and ARBs, did not alter the risk of COVID-19 ( Vila-Corcoles et al, 2020 ). Similarly, in a recent study analyzing 6,272 COVID-19 patients, no association between the use of ACE-Inhs.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 89%
“…In a population based retrospective study of 34,936-hypertensive adults, the use of antihypertensive drugs, including diuretics, CCBs, βARBs, ACE-Inhs. and ARBs, did not alter the risk of COVID-19 ( Vila-Corcoles et al, 2020 ). Similarly, in a recent study analyzing 6,272 COVID-19 patients, no association between the use of ACE-Inhs.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 89%
“…With conflicting mechanistic evidence concerning risk of SARS‐CoV‐2 from some of the most widely used drugs for cardiovascular disease, HT and diabetes, an urgent request for epidemiologic evidence was issued to attempt to determine the role of RAS inhibitors in relation to SARS‐CoV‐2 severity 1 . To date, several studies of hospitalized (HT) COVID‐19 patients suggest no association with severe infections or mortality 11–15 …”
Section: Introductionmentioning
confidence: 99%
“…1 To date, several studies of hospitalized (HT) COVID-19 patients suggest no association with severe infections or mortality. [11][12][13][14][15] In this community-based case-control study of central Massachusetts COVID-19 patients, we investigated whether RAS inhibitors exposure increased the risk of severe sequelae defined as hospitalization or death. Additionally, we investigated the novel hypothesis that the diuretic thiazide, often prescribed for HT in conjunction with RAS inhibitors, may modify the risk of severe SARS-CoV-2.…”
mentioning
confidence: 99%
“…Six studies [1][2][3][4][5][6] including 318 261 participants reported data on PPI usage and the risk of SARS-CoV-2 infection. Among them, five studies had information of current PPI users compared with nonusers and four on past PPI users versus non-users.…”
Section: Do Proton Pump Inhibitors Influence Sars-cov-2 Related Outcomentioning
confidence: 99%
“…Analysis of five studies [1][2][3][4][5] encompassing 145 428 patients who were tested for SARS-CoV-2 showed that the risk of SARS-CoV-2 infection was higher, although not significantly, among current PPI users (OR 1.33, 95% CI 0.86 to 2.07, p=0.20; figure 1) compared with PPI non-users, with evidence of substantial between-study heterogeneity (I 2 =97%). Moreover, in a subgroup analysis of non-Korean cohorts, [2][3][4] we found a significant association between current use of PPIs and increased risk of SARS-CoV-2 infection (OR 1.94, 95% CI 1.59 to 2.36, p<0.0001; online supplemental figure 2). Furthermore, a leave-one-out sensitivity analysis revealed that the summary estimate of the association between current PPI usage and SARS-CoV-2 infection was overly influenced by a single Korean study 5 (online supplemental figure 3).…”
Section: Do Proton Pump Inhibitors Influence Sars-cov-2 Related Outcomentioning
confidence: 99%